Analysis of E-SPT and E-filing utilization on taxpayer compliance: A multiple regression approach - Rinaldi, Achi; Devi, Yulistia; Salih, Dana Taha Mohammed (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: Statistical data from Lampung Province indicate a steady annual increase in the number of taxpayers utilizing e-SPT (electronic tax return) and e-filing, particularly from 2019 to 2022.Aim: This study aims to analyze the effect of e-SPT usage on taxpayer compliance, investigate the impact of e-filing on taxpayer compliance, assess the combined effects of e-SPT and e-filing on taxpayer compliance, and understand taxpayer compliance within the framework of Islamic Economics.Method: Taxpayers from the Bandar Lampung Tax Office (KPP) were selected as respondents. A random sampling technique was employed to gather data from 100 participants. The data were analyzed using multiple linear regression analysis with SPSS.Results: The findings reveal that the convenience, effectiveness, and satisfaction derived from using e-SPT and e-filing, along with an analysis of Annual Tax Returns, significantly influence taxpayer compliance. The use of e-SPT alone has a notable impact on compliance, as does the use of e-filing. Furthermore, the combined usage of e-SPT and e-filing has a significant collective impact on taxpayer compliance.Conclusion: The study concludes that both e-SPT and e-filing are critical in enhancing taxpayer compliance, with their combined application having a more substantial effect. These findings also offer insights into taxpayer compliance from the perspective of Islamic Economics, emphasizing the role of modern tax administration tools in promoting compliance.